Face and construct validity of TU-Delft epidural simulator and the value of real-time visualization. Issue 3 (March 2019) - Zivkovic, Nenad; van Samkar, Ganapathy; Hermanns, Henning; Lirk, Philipp; Hollmann, Markus W; van den Dobbelsteen, John J; van Gerwen, Dennis J; Stevens, Markus F
Abstract : Background and objectives: Learning epidural anesthesia traditionally involves bedside teaching. Visualization aids or a simulator can help in acquiring motor skills, increasing patient safety and steepening the learning curve. We evaluated the face and construct validity of the TU-Delft Epidural Simulator and the effect of needle visualization. Methods: Sixty-eight anesthesiologists, anesthesia residents, and final-year medical students tested the epidural simulator. Participants performed six epidural simulations with and six without needle visualization. We tested face validity on a Likert scale questionnaire. We collected data with the simulator software (spinal taps, dura contacts, bone contacts, attempts, and time) and tested for correlation with the performer's experience (construct validity). A visualization aid was tested in a randomized crossover design. Results: Face validity as rated by the participants was above average, with a mean of 3.7 (2.0–4.8) on a 5-point scale. Construct validity was indicated by significantly more spinal taps (0.4 [0–4) vs 0.07 [0–2], p=0.04) and more dura contacts (0.58 [0–6] vs 0.37 [0–3], p=0.002) by the inexperienced group compared with the expert group. The visualization aid improved performance by reducing the number of bone contacts and the number of attempts, and by decreasing the procedure time. Prior visualization training reduced the total procedure time from 279 s (69–574) to 180 s (53–605) (p = 0.01) for the "blind" procedure. Conclusions: The TU-Delft Epidural Simulator is a useful tool for teaching motor skills during epidural needle placement. Prior use of a visualization tool improves performance even without visual support during consequent simulations.